Habitat compression and ecosystem shifts as potential links between marine heatwave and record whale entanglements - Jarrod A. Santora (Nature Portfolio, 2020)
Climate-driven extreme events may have strong local impacts on marine organisms and fisheries. Here the authors report increased whale entanglements in the northeast Pacific following a marine heatwave, and propose compression of coastal upwelling habitat as the potential driver.